Subthalamic nucleus stimulation–induced local field potential changes in dystonia - Wiest, C; Morgante, F; Torrecillos, F; Pogosyan, A; He, S; Baig, F; Bertaina, I; Hart, MG; Edwards, MJ; Pereira, EA; Tan, H (Wiley, 2022)
Background Subthalamic nucleus (STN) stimulation is an effective treatment for Parkinson's disease and induced local field potential (LFP) changes that have been linked with clinical improvement. STN stimulation has also been used in dystonia although the internal globus pallidus is the standard target where theta power has been suggested as a physiomarker for adaptive stimulation.